FAKTOR YANG MEMPENGARUHI PENDAPATAN PEDAGANG KAKI LIMA DI BOJONEGORO - Fatkur Muin (Jurnal Manajemen dan Penelitian Akuntansi (JUMPA), 2012)
This research is a research survey conducted on a group of street vendors in the city districts Bojonegoro based on data obtained from the Civil Service Police Unit Bojonegoro. Of the total number of street hawkers in the city district Bojonegoro, research has focused on the 5 (five) community of street vendors in urban districts Bojonegoro. Being a street vendor is an option and of course the choice was based on some of them which are of necessity, to be independent, want to find a fortune that was lawful, to support his family